KAIDAH FIKIH: SEJARAH DAN PEMIKIRAN EMPAT MAZHAB - Sandy Rizki Febriadi Sanusi (Prodi Hukum Keluarga Islam (Ahwal Asy-Syakhsiyyah) Fakultas Syariah Unisba, 2021)
The rules in Islamic science which have a systematic form and cover the laws under its auspices aim to make it easier for mujtahids to respond to current problems. The rules of fiqh are arranged in a certain period of time. These rules were only compiled systematically at a later date in accordance with developments and growth ijtihad among experts and founders of schools. This study aims to: first, describe and explain the benefits of fiqh rules. Second, knowing the history of the development of jurisprudence. Third, describe the fiqh rules according to the four schools of thought and the levelization of fiqh rules. This research is a qualitative research with a descriptive analysis study that uses a library research approach. The result of the research is that the rules of fiqh are something that is global or universal which can include certain things. Second, the history of the development of fiqh can be divided into three periods, namely, the period of formation and, the period of development and preparation, and the growth of the period of improvement. Third, the jurists of the four schools of law say that the rules of fiqh can be used as a source of Islamic law and can be applied to contemporary problems. The problems that arise between the four schools of law make the rules of fiqh an independent argument without being supported by the Qur'an and Sunnah. When the rules of fiqh are not supported by these two main sources, the scholars do not use them as a source of Islamic law. Keywords: Rules, Law, Jurisprudence, Islam.